Influence of process parameters on tensile properties of direct energy deposition samples - Tan, Zheng Jie (Nanyang Technological University, 2024)
Additive Manufacturing (AM) has emerged as a transformative technology revolutionizing traditional manufacturing processes, and it has since been implemented in many different industries due to the benefits the method has. Among the manufacturing methods within the AM domain, the one that stands out is Direct Energy Deposition (DED), an additive process that deposits material layer by layer using a focused energy source. This final year project report aims to find out the impact of the variation in process parameters on the tensile properties of the 316L stainless steel parts fabricated through the DED method. A dataset with a variation in the process parameters was used to produce twenty 316L stainless steel samples using the DED method, which went through tensile test to determine how the variation of the process parameters affects the tensile properties. The main process parameters to be investigated are Laser Power (LP), Scanning Speed (SS), Powder Mass Flow Rate (PMFR), XY-incremental ratio (XY), and Z-incremental ratio (Z). The tensile properties to be studied are Ultimate Tensile Strength (UTS), Young’s Modulus, Yield Strength, and Elongation. Design of Experiment (DOE) and Analysis of Variance (ANOVA) were utilized through the Minitab software to analyze the relationship between the factors and responses of the experiment. The process parameters, LP and XY were found to be the dominant process parameters that can affect both UTS and Yield Strength individually, while there were not any significant parameters affecting Young’s Modulus and Elongation. An increase in both LP and XY individually causes an increase in both UTS and Yield Strength. Combination of parameters with huge significance to UTS are SS*PMFR, PMFR*Z and XY*Z, with PMFR*Z being the highest (P-value = 0.028, F-value = 15.89) at PMFR = 16 and Z = 1.4. Combination of parameters with huge significance to Yield Strength are LP*SS and PMFR*Z with PMFR*Z being the highest (P-value = 0.007, F-value = 43.21) at PMFR = 16 and Z = 1.4.